2020
DOI: 10.2478/amns.2020.1.00018
|View full text |Cite
|
Sign up to set email alerts
|

Global Attractors for the Higher-Order Evolution Equation

Abstract: In this paper, we obtain the existence of a global attractor for the higher-order evolution type equation. Moreover, we discuss the asymptotic behavior of global solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The characteristics of independent learning are significantly different in the measurement of consciousness of independent learning. There was no significant difference in learning attitude [8]. There was no significant difference in the concept of learning.…”
Section: Comparative Study On Autonomous Learning Abilitymentioning
confidence: 75%
“…The characteristics of independent learning are significantly different in the measurement of consciousness of independent learning. There was no significant difference in learning attitude [8]. There was no significant difference in the concept of learning.…”
Section: Comparative Study On Autonomous Learning Abilitymentioning
confidence: 75%
“…In [3], the authors showed the exponential growth of solution for the equation (1.5). In recent years, some other authors investigate hyperbolic type equations (see [10,11,12,13,14,15,16,17,18,19,20,21]).…”
Section: Introductionmentioning
confidence: 99%